Sex life after 60: risk or prevention against sexually transmitted infections (Research, Society and Development, 2023)
The population is in the process of aging and with the maintenance of sexual practices, the risk of acquiring Sexually Transmitted Infections becomes high. The objective of this investigation is to discuss the knowledge and behavior of the elderly regarding the risk and prevention of sexually transmitted infections. Quantitative, descriptive and cross-sectional study carried out in the city of Teresópolis/RJ, in the year 2021. The participants were fifty elderly people registered in a Family Health Unit. For data collection, a structured self-administered questionnaire was used. Among the participants, more than half are male, aged between 60 and 65 years, married, self-declared white, Catholic, with incomplete elementary schooling. More than half did not receive guidance from health professionals regarding prevention and mentioned the use of television as a way of acquiring information. As for knowledge, the majority report not knowing what a sexually transmitted disease is, they do not use condoms and recognize the risk of contagion. This study showed that the elderly population faces barriers regarding their sexuality and that among the factors associated with susceptibility to infections are: low education, limited knowledge about contagion and prevention and poor adherence to condom use. We call for educational campaigns and for the effective participation of health professionals in comprehensive care in order to minimize damage to the sexual health of the elderly.